2006
DOI: 10.1113/jphysiol.2005.104174
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants reverse depression of the hypoxic ventilatory response by acetazolamide in man

Abstract: The carbonic anhydrase inhibitor acetazolamide may have both inhibitory and stimulatory effects on breathing. In this placebo-controlled double-blind study we measured the effect of an intravenous dose (4 mg kg −1 ) of this agent on the acute isocapnic hypoxic ventilatory response in 16 healthy volunteers (haemoglobin oxygen saturation 83-85%) and examined whether its inhibitory effects on this response could be reversed by antioxidants (1 g ascorbic acid I.V. and 200 mg α-tocopherol P.O.). The subjects were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…An inhibitory effect, however, is not supported by the finding that both in normoxia and hypoxia acetazolamide increases ventilation (36,41). This is clearly different from the effect of intravenous administration in both animals and humans when acetazolamide, in a dose too low to have direct effects on the central nervous system, has inhibitory effects on both the hypoxic response and the O 2 -CO 2 interaction (36,40,42). Why in humans an inhibitory effect seems solely present after acute administration aimed at reaching equal plasma levels of the agent (36) remains unclear.…”
Section: Expressing Hypoxic Sensitivity Asmentioning
confidence: 74%
See 1 more Smart Citation
“…An inhibitory effect, however, is not supported by the finding that both in normoxia and hypoxia acetazolamide increases ventilation (36,41). This is clearly different from the effect of intravenous administration in both animals and humans when acetazolamide, in a dose too low to have direct effects on the central nervous system, has inhibitory effects on both the hypoxic response and the O 2 -CO 2 interaction (36,40,42). Why in humans an inhibitory effect seems solely present after acute administration aimed at reaching equal plasma levels of the agent (36) remains unclear.…”
Section: Expressing Hypoxic Sensitivity Asmentioning
confidence: 74%
“…Details of measuring ventilation, respiratory gases, and oxygen saturation and the technique of dynamic end-tidal forcing are provided elsewhere (40,41).…”
Section: Subjects and Apparatusmentioning
confidence: 99%
“…In humans, metabolic acidosis normally leads to an increase in ventilation, for which the peripheral chemoreceptors may be responsible (26,27,30,36). Already at low doses, ACTZ largely reduced the ventilatory response to hypoxia in humans and cats (35,37), but even a high dose of the much more effective CA inhibitor MTZ entirely failed on that score at least in cats (34). In the same species, only ACTZ, but not MTZ, diminished also the CO 2 sensitivity of the peripheral chemoreflex loop (3).…”
Section: Discussionmentioning
confidence: 99%
“…7,[20][21][22] It is concerned that antioxidants may interfere with the action of ACZ on the normocapnic hypoxic ventilatory response. 23) In our work we chose ACZ as a positive drug to compare the effects of HPN with ACZ. The first step of the present study was to prepare the free radical scavenger by literature reported procedures.…”
mentioning
confidence: 99%